Algoritma Triple Exponential Smoothing Untuk Prediksi Trend Turis Pariwisata Jatim Park Batu Saat Pandemi Covid-19 - Safor Madianto; Ema Utami; Anggit Dwi Hartanto (Politeknik Negeri Batam, 2021)
The level of tourism visits in 2021 both local and foreign to Indonesian tourism has decreased drastically. The COVID-19 pandemic is one of the causes of this loss. In the last 1 year, the level of tourism has dropped dramatically due to this pandemic. The impact on a country is an economic recession, Singapore is a country that is experiencing a severe recession of up to -40%, a country is a country that also depends, one of which is on tourism. Jatim Park Batu is a tourism learning park and family recreation area in Batu, East Java. Jatim Park is a well-known tourism object in East Java. The uncertainty of the number of tourists each month affects the operational management of Jatim Park in making every decision, both technical and strategic decisions. The researcher proposes to use the Triple Exponential Smoothing algorithm, the Holt Winters model, where this algorithm is classified as a prediction algorithm that can consider trend and seasonal factors. The method of measuring accuracy uses the MAPE (Mean Absolute Percetage Error) method. Tests were carried out by initiating the alpha beta gamma parameter 30 times and obtained an average of 9%.